We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
623
1
avatar

Let $$h(x) = f(g(x)).$$ Note that $f(x)$ and $g(x)$ are not necessarily polynomials. State for each of the following cases whether $h(x)$ is even, odd, or neither.

 

a) $f(x)$ and $g(x)$ are both even.

b) $f(x)$ and $g(x)$ are both odd.

c) $f(x)$ is even and $g(x)$ is odd.

d) $f(x)$ is odd and $g(x)$ is even.

 Apr 3, 2018
 #1
avatar+349 
+3

a) If both f and g are even, then \(h(x)=f(g(x))=f(g(-x))=h(-x)\)EVEN

b) If both and are odd, then \(h(-x)=f(g(-x))=f(-g(x))=-f(g(x))=-(h(x))\)ODD

c) If f is even and g is odd, then \(h(-x)=f(g(-x))=f(-g(x))=f(g(x))=h(x)\)EVEN

d) If f is odd and g is even, then \(h(x)=f(g(x))=f(g(-x))=h(-x)\)EVEN

 

smiley

 Apr 3, 2018

5 Online Users

avatar